PENGARUH KOMPOSISI PUPUK KS, ZA, DAN UREA, SERTA DOSIS N TERHADAP MUTU TEMBAKAU BESUKI NO - MOCHAMMAD SHOLEH; ABDUL RACHMAN; MACHFUDZ MACHFUDZ (Jurnal Penelitian Tanaman Industri, 2000)
Effect of KS, AS, and urea Compositions and N-dosages on quality of Besuki cigar tobaccoThe experiment was conducted on loamy soil at Ajung, Jember from June 1999 to March 2000. The objective was to study the effect of Kalk Salpetcr (KS), ammonium sulphates (AS), and urea compositions and N-dosages on quality of Besuki cigar tobacco. The treatment consisted of two factors i.e. fertilizer composition and N dosages. The first factor was 5 levels of fertilizer composition, i.e. KS; KS(50%)+AS (50%); AS; KS(50%)+urea (50%) and uea. The second factor was 3 level of N-dosages, i.e. 60, 90 and 120 kg N/ha. The treatments were arranged in factorially randomized block design with 3 replications. Planting space was double row (100+70) cm x 40 cm wiUi a population of 168 plants per plot. Results showed thai AS or urea as side dressing fertilizer was not significantly different from KS fertilizer on the percentage of warpper (dekblad) and binder (omblad) quality, leaf thickness, and burning capacity. But especially on organolcptic AS or urea as side dressing fertilizer decreased organoleptic quality, i.e. the taste was bitter and irritating, less aromatic, bad smell, ash color changed from white to black, and decreased ash resistance. All of those characteristics were not desirable in cigar factory. Based on organolcptic quality we suggest the following : (I) AS and urea should be used as a starter only not as side dressing fertilizer, (2) KS fertilizer still perform Ihe best result (3) recommended N-dosage was 60 kg N/ha.